MEASUREMENT OF WHITENESS OF MATERIALS BY OPTICAL ELECTRONIC METHOD - Karimov Abdusamat Ismonovich; Ismanov Mukhammadziyo Abdusamat ugli (Galaxy International Interdisciplinary Research Journal, 2022)
One of the laser measurement systems is the Monarc system. This measurement system is designed to measure the rotational position, linear dimensions and shape of the object being inspected using a laser. The Monarc system includes a specially programmed automatic product quality control system. Keywords: Monarc, Laser